Race and ethnicity matter! Moving Parkinson’s risk research towards diversity and inclusiveness - Sara Siddiqi; Zoe Ortiz; Stephanie Simard; Juan Li; Kamaya Lawrence; Melissa Redmond; Julianna J. Tomlinson; Michael G. Schlossmacher; Natalina Salmaso (npj Parkinson's Disease)
Abstract Parkinson’s disease (PD) is a prevalent neurodegenerative disorder that shows considerable heterogeneity of risk factors however, the degree to which race/ethnicity has been actively pursued in PD risk research is unknown. We examined PD literature from 2000–24 and found that less than half accounted for race/ethnicity and only 4.8% of n = 1142 articles included ethno-racial factors as an integral part of the analysis. This demonstrates that race/ethnicity has been critically understudied in PD and further studies that examine ethno-racial contributions to risk for PD are warranted.